Development of Human Capital through the Islamic Education of Our Brothers (Mu’alaf) in Terengganu - Norhana Abdullah @ Ng Siew Boey; Mastor, Khairul Anwar; Muhamat @ Kawangit, Razaleigh; Awang, Azarudin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Development of human capital refers to the changes upon individuals to attain high moral values, be cultured in manners, have healthy mental intellect, be and able to perform their duty as a caliph in this world. In view of this, Islamic education plays an important role in developing the spirituality of the community of our brothers (mu’alaf). Thus, the objective of this study is to identify the real appreciation of the Islamic education of our brothers and to identify the relationship between Islamic education and the development of the human capital of our brothers in Terengganu. This study uses a qualitative method with a purposive sampling technique in focus group discussion. The result of the study shows that the level of understanding and religiosity appreciation among our brothers in Terengganu is still weak. This study suggests that more effective Islamic education must be reinforced by focusing on the teaching methods carried out. This study is important because it conveys real information on the learning situation and religious appreciation of our brothers in Terengganu which will fill the gap of previous studies.